Proceedings of the 50th Hawaii International Conference on System Sciences (2017) 2017
DOI: 10.24251/hicss.2017.262
|View full text |Cite
|
Sign up to set email alerts
|

Is Aggression Contagious Online? A Case of Swearing on Donald Trumps Campaign Videos on YouTube

Abstract: This study explores whether aggressive text-based interactions in social media are contagious. In particular, we examine swearing behaviour of YouTube commentators in response to videos and comments posted on the official Donald Trump's campaign channel. Our analysis reveals the presence of mimicry of verbal aggression. Specifically, swearing in a parent comment is significantly and positively associated with the likelihood and intensity of swearing in subsequent 'children' comments. The study also confirms th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 45 publications
(82 reference statements)
0
20
0
2
Order By: Relevance
“…This can be proved by the study that has been done by Kwon and Gruzd (2017) where a study was done on a set of YouTube videos based on Donald Trump's campaign channel. This study investigates whether forceful comments and swearing on YouTube content is in fact infectious and contagious.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be proved by the study that has been done by Kwon and Gruzd (2017) where a study was done on a set of YouTube videos based on Donald Trump's campaign channel. This study investigates whether forceful comments and swearing on YouTube content is in fact infectious and contagious.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study by Kwon and Gruzd (2017), on swearing behaviour n YouTube revealed that one of the reason for aggressive and emotional texts on YouTube is due to the fact that most of its users are anonymous. This study examined comments on the official Donald Trump's channel and proved that anonymity is also one of the reason for the users of YouTube to spread hostility on this site.…”
Section: Introductıonmentioning
confidence: 99%
“…Unlike the paper "Is Aggression Contagious Online? A Case of Swearing on Donald Trump's Campaign Videos on YouTube" [3] that was published in this minitrack last year and which examined the contagion of aggression, Kim and Herring study the contagion of politeness in public forums. Specifically, they studied it in the context of reader comments in Korean news websites, websites that are plagued by insensitive and inconsiderate reader comments.…”
Section: This Year's Papersmentioning
confidence: 99%
“…Research on online verbal abuse has examined user-generated comments in blogs [2,10], news websites [8,11,20], and YouTube [22], mostly focusing on the concept of incivility, which appears closely related to impoliteness. Although the two concepts are often used interchangeably in everyday conversation, they are conceptualized in distinct ways in the literature.…”
Section: Politeness and Participation In Online Public Discoursementioning
confidence: 99%